2022
DOI: 10.1111/joim.13560
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing the immune response over 15 months after SARS‐CoV‐2 infection: A longitudinal population‐wide study in the Faroe Islands

Abstract: Background The durability of SARS‐CoV‐2 antibody response and the resulting immunity to COVID‐19 is unclear. Objectives To investigate long‐term humoral immunity to SARS‐CoV‐2. Methods In this nationwide, longitudinal study, we determined antibody response in 411 patients aged 0–93 years from two waves of infections (March to December 2020) contributing 1063 blood samples. Each individual had blood drawn on 4–5 occasions 1–15 months after dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
9
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 31 publications
2
9
1
Order By: Relevance
“…Overall, we demonstrated that even after the booster dose, health professionals can become reinfected with new variants of SARS-CoV-2. Therefore, our study demonstrates that prolonged protection after COVID-19 infection, even after the booster dose, does not prevent reinfection by new variants, which contrasts with the prolonged immune response cited by other studies (66,80). Studies show that previous infection and booster dose reduce the risk of reinfection, as seen in Switzerland (81), Qatar (61), and United States of America (82).…”
Section: Discussioncontrasting
confidence: 80%
See 2 more Smart Citations
“…Overall, we demonstrated that even after the booster dose, health professionals can become reinfected with new variants of SARS-CoV-2. Therefore, our study demonstrates that prolonged protection after COVID-19 infection, even after the booster dose, does not prevent reinfection by new variants, which contrasts with the prolonged immune response cited by other studies (66,80). Studies show that previous infection and booster dose reduce the risk of reinfection, as seen in Switzerland (81), Qatar (61), and United States of America (82).…”
Section: Discussioncontrasting
confidence: 80%
“…Even though age was not associated with reinfection, we observed that the dynamics of antibody levels varied over time and behaved differently across age groups. The level of antibodies produced by the younger group was lower than the older groups, as observed by others works (66,72,73) Many studies have sought to understand and relate antibody profiles and Ct values with disease severity and protection against reinfection (27,33,74,75). Omid Dadras et al, 2022 (76), concluded that the relationship between viral load and disease severity is inconclusive.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Previous study reported the circulating antibody levels in male were initial higher but more marked decrease. 38 However, our study only focused on the effects of sex factor on neutralizing antibodies in sera collected at 2–4 weeks after infection, the more information about the dynamics of humoral immunity should be investigated in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, smokers may have avoided infection-prone settings due to awareness of their increased risk of severe disease. However, several studies have suggested that smoking is associated with overall reduced levels of IgA, IgG and IgM titers, and of IgG following SARS-CoV-2 infection or COVID-19 vaccination, 55 , 56 , 57 , 58 , 59 hence a lower seroprevalence among smokers could be an artefact.…”
Section: Discussionmentioning
confidence: 99%